Pengaruh Efektivitas dan Kontribusi Penerimaan Pajak Daerah Terhadap Pendapatan Asli Daerah Kabupaten Bandung - Rina Amalia Putri Wahyuni; Khozin Arief (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This research is a quantitative descriptive research. This research aims to determine the level of effectiveness and contribution of local taxes to the Local Government Revenue of Bandung District. Subjects in this research is Bandung District and Local Government Revenue in 2015-2019. This research was conducted by using quantitative methods with a descriptive approach. Sample in this research is 60 months from January 2015 to December 2019. Multiple linear regression was used in data analysis using SPSS Version 25.0. The results of this study indicate that the Effectiveness of Local Taxes (X1) partially has no significant and positive effect on local government revenue (Y). While the Local Tax Contribution (X2) is partially positive and significant effect on Local Government Revenue (Y) of 23,24%. Simultaneously the Effectiveness and Contribution of Local Taxes affect on Local Government Revenue was 25,6% while 74,4% was influenced by other causes outside this research.